Part of plant to sample leaves for nutritional status evaluation in soursop (Annona muricata L.) - Silva de Lima, Rosiane de Lourdes; Ferreira, Gilvan Barbosa; Weber, Olmar Baller; Cazetta, Jairo Osvaldo [UNESP] (Univ Federal Lavras-ufla, 2007)
The lack of information in literature about leaf sampling soursop plant in particular, the definition of the leaf position at the tree top and leaves on the branches is still a limiting factor for the diagnosis of this cultivation. Aiming to determine which is the suitable part of the plant for leaf sampling and evaluate the nutritional status of the soursop plants, an experiment was developed on the experimental farm Embrapa - CNPAT, at Pacajus-CE, in the period from March to April, 2003. One collected leaves from three positions at the top (upper third, medium third and lower third) and three positions on the branches (apical part leaves, basal and medium) and one determined the tenor of P, K, Ca, Mg, S, Fe, Cu, Zn and Mn. The results allow to suggest that the mineral levels of the medium part of leaves at the top of the trees on the medium position of the branch, reflect best nutritional status of the plant.
Keywords: Annona muricata; mineral nutrition; position in the top of trees